(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
In bioethical issues, the major role played by the self-determination principle in the decision- making process has completely redefined the hierarchy of principles inspiring medical profession. Concretely, this means that in principle the decisional power is no longer exclusively exercised by doctors according to the well-known paternalistic model. In the new scenario, where self-determination plays a key role in health care relationships, the patient has the definitive say on acceptance or refusal of medical treatments. In fact, not only has the self-determination principle gained widespread acceptance and plays a leading role in ethical theories and medical ethics, but it has been legally ruled. The self-determination principle has undergone a paradigmatic process of extension and specification also with regard to minors’ participation in the decision-making process at the end-of life. The aim of the paper is to restate the ethical and legal status of minors as regards decisions at the end of life. The first step will be contextualization of this extension with regard to decisions concerning minors’ health within the framework of the European continental legal tradition. Second, the analysis will focus on the main legally binding and non-binding documents that contribute to outlining minors’ rights at the end of life. Finally, it will argue that whenever minors are involved in sad and painful decisions like the ones at the end of life, parents or the legal representative and physicians should always try to include them in the decision-making process, that is, to decide ’with’ and not ’for’ the minor.